Extracellular vesicles and melanoma: New perspectives on tumor microenvironment and metastasis - Benito-Martín, Alberto; Jasiulionis, Miriam Galvonas; García-Silva, Susana (Frontiers in Cell and Developmental Biology, 2023)
Secreted extracellular vesicles (EVs) are lipid bilayer particles without functional nucleus naturally released from cells which constitute an intercellular communication system. There is a broad spectrum of vesicles shed by cells based on their physical properties such as size (small EVs and large EVs), biogenesis, cargo and functions, which provide an increasingly heterogenous landscape. In addition, they are involved in multiple physiological and pathological processes. In cancer, EV release is opted by tumor cells as a beneficial process for tumor progression. Cutaneous melanoma is a cancer that originates from the melanocyte lineage and shows a favorable prognosis at early stages. However, when melanoma cells acquire invasive capacity, it constitutes the most aggressive and deadly skin cancer. In this context, extracellular vesicles have been shown their relevance in facilitating melanoma progression through the modulation of the microenvironment and metastatic spreading. In agreement with the melanosome secretory capacity of melanocytes, melanoma cells display an enhanced EV shedding activity that has contributed to the utility of melanoma models for unravelling EV cargo and functions within a cancer scenario. In this review, we provide an in-depth overview of the characteristics of melanoma-derived EVs and their role in melanoma progression highlighting key advances and remaining open questions in the field.